2014
DOI: 10.1007/s00330-014-3427-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of the solid component in pulmonary subsolid nodules by semiautomatic segmentation

Abstract: Objective To determine whether semiautomatic volumetric software can differentiate part-solid from nonsolid pulmonary nodules and aid quantification of the solid component. Methods As per reference standard, 115 nodules were differentiated into nonsolid and part-solid by two radiologists; disagreements were adjudicated by a third radiologist. The diameters of solid components were measured manually. Semiautomatic volumetric measurements were used to identify and quantify a possible solid component, using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 24 publications
4
46
0
1
Order By: Relevance
“…Thanks to the development of specific software, volumetric measurement of SSNs has become accurate over the years with a successful segmentation of up to 97% of the nodules [75,[78][79][80]. Similar results have been reported in the detection and segmentation of PSNs and, interestingly, a quantification of the solid component was related to pathological prognostic factors, such as lymphatic, vascular and pleural invasion [75,81,82].…”
Section: Factors Influencing Nodule Measurement Variationssupporting
confidence: 64%
See 1 more Smart Citation
“…Thanks to the development of specific software, volumetric measurement of SSNs has become accurate over the years with a successful segmentation of up to 97% of the nodules [75,[78][79][80]. Similar results have been reported in the detection and segmentation of PSNs and, interestingly, a quantification of the solid component was related to pathological prognostic factors, such as lymphatic, vascular and pleural invasion [75,81,82].…”
Section: Factors Influencing Nodule Measurement Variationssupporting
confidence: 64%
“…Notably, the latter is due to a better capability of detecting the appearance or progression of a solid component in SSNs [131]. The usefulness of the system has been proven afterwards by other experimental studies [78,81,132] and used in the discrimination of histological subtypes in adenocarcinoma [133]. As for volumetric measurement, an existing interscan variability has been described for nodule mass assessment, and an increase in nodule mass of 30% has been regarded as a significant growth [134].…”
mentioning
confidence: 99%
“…Third, we investigated solid and subsolid nodules and did not discriminate further between semi-solid and groundglass nodules. One of the most important questions related to detection sensitivity for these nodules is agreement regarding the presence or absence of a solid component, with disagreement reaching as much as 12% in conventional low-dose CT. 26 Fourth, measurements of attenuation and size have not been performed. Increased variation of diameters and mass is a real concern when decreasing dose levels to the levels attempted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, we focus more on solid NSCLC, even though some cases of reduced attenuation like cavitation are still evaluated. Other types of reduced attenuation such as ground glass opacity (GGO) and reticulation are particularly avoided, since earlier studies demonstrated high errors of computerā€assisted segmentation when evaluating subā€solid nodules, especially the GGO case . The gold standard for these cases would be manual delineations by an expert radiologist, though we do believe a sophisticated algorithm like deep learning which has recently gained tremendous interest from the medical imaging community, could provide a solution.…”
Section: Introductionmentioning
confidence: 99%